Knowledge, attitude, and practice of a local community towards the prevention and control of rabies in Gaibandha, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: Knowledge, attitude, and practice (KAP) of rabies in the community are essential for developing post-exposure behavioral treatment and for understanding current prevention and control policy on rabies. This was a cross-sectional study in Gaibandha Sadar, a northern district of Bangladesh, investigating the level of KAP about rabies.  Materials and methods: A total of 368 interviewed respondents, of whom 280 (76.09%) were male, and 88 (23.91%) were female. A structured questionnaire was used for the data collection from respondents on socio-demographic information and KAP regarding rabies. The data analyzed with STATA-IC-11.0 and the association of independent variables with rabies KAP scores were calculated using Pearson’s Chi-square.  Results: Most respondents had adequate KAP levels and positive thoughts on rabies prevention. The KAP scores were strongly associated with education and employment status (p < 0.05). Most respondents said that stray dogs are a headache in the area and believed that control of the dog population in Gaibandha is essential.  Conclusion: These outcomes also revealed that there is an information gap about rabies that might improve by developing an education program for awareness.J. Adv. Vet. Anim. Res., 7(3): 414-420, Sep 2020http://doi.org/10.5455/javar.2020.g436